2017
DOI: 10.1186/s13287-017-0632-0
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from embryonic mesenchymal stem cells alleviate osteoarthritis through balancing synthesis and degradation of cartilage extracellular matrix

Abstract: BackgroundMesenchymal stem cell therapy for osteoarthritis (OA) has been widely investigated, but the mechanisms are still unclear. Exosomes that serve as carriers of genetic information have been implicated in many diseases and are known to participate in many physiological processes. Here, we investigate the therapeutic potential of exosomes from human embryonic stem cell-induced mesenchymal stem cells (ESC-MSCs) in alleviating osteoarthritis (OA).MethodsExosomes were harvested from conditioned culture media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
304
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(311 citation statements)
references
References 40 publications
7
304
0
Order By: Relevance
“…The therapeutic effect of MSC‐derived exosomes on arthritis have also been investigated. In several studies, intravenous or intra‐articular exosomes isolated from MSCs were shown to inhibit macrophage activation, inflammation, and cartilage destruction in in vitro and in vivo models via inhibition of catabolisis, inflammatory markers and apoptosis, increase of collagen type II synthesis, and modulation of T and B cells …”
Section: Role Of Exosomesmentioning
confidence: 99%
“…The therapeutic effect of MSC‐derived exosomes on arthritis have also been investigated. In several studies, intravenous or intra‐articular exosomes isolated from MSCs were shown to inhibit macrophage activation, inflammation, and cartilage destruction in in vitro and in vivo models via inhibition of catabolisis, inflammatory markers and apoptosis, increase of collagen type II synthesis, and modulation of T and B cells …”
Section: Role Of Exosomesmentioning
confidence: 99%
“…Immunohistochemical staining was conducted following a standard protocol (Y. Wang, Yu, Liu, et al, 2017). Cartilage matrix was detected using type II collagen (COL II) and aggrecan.…”
Section: Immunohistochemistry and Immunofluorescencementioning
confidence: 99%
“…Haomin Cui et al reported that exosomes containing miRNA derived from macrophages induce peritendinous fibrosis healing after tendon injury. Yafei Wang and S. Zhang et al revealed that exosomes from embryonic MSCs alleviate osteoarthritis through balancing synthesis and degradation of cartilage extracellular matrix. Myeongsik Oh et al illustrated that exosomes derived from human induced pluripotent stem cells ameliorate the aging of skin fibroblasts.…”
Section: Discussionmentioning
confidence: 99%